PROSES TERBENTUKNYA ALAM SEMESTA DALAM PERSPEKTIF TEORI BIG BANG DAN KOSMOLOGI IBN SINA - Muliatul Hamidah; Grisly Fatmawati; Bintang Julita Sulistya Putri (Al-Iqro', 2026)
This study aims to analyze the concept of the origin of the universe according to the Big Bang Theory and Ibn Sina's cosmology, as well as to identify the similarities and differences between the two. The study seeks to understand how modern science and Islamic philosophy explain the formation of the universe through different approaches while exploring the possibility that these perspectives complement one another. This research employs a qualitative method using a library research approach. The data were collected from various sources, including books, scientific articles, journals, and other relevant literature discussing the Big Bang Theory, Ibn Sina's cosmology, and the relationship between science and Islamic thought. The collected data were analyzed using a descriptive-comparative method to identify the similarities, differences, and relevance of both concepts. The findings indicate that both the Big Bang Theory and Ibn Sina's cosmology provide rational explanations for the origin of the universe and acknowledge the existence of order in the process of its formation. However, they differ fundamentally in their approaches. The Big Bang Theory is based on empirical observations and explains the physical process of the universe's formation through the expansion of an extremely hot and dense initial state. In contrast, Ibn Sina's cosmology explains the origin of the universe through the metaphysical and philosophical concepts of Wājib al-Wujūd (Necessary Existent), Mumkin al-Wujūd (Contingent Existent), and the theory of emanation. This study concludes that these two perspectives should not be viewed as contradictory; rather, they can be understood as complementary approaches to explaining the origin and existence of the universe.